2000
DOI: 10.1007/s002130050046
|View full text |Cite
|
Sign up to set email alerts
|

The discriminative stimulus properties of the atypical antipsychotic olanzapine in rats

Abstract: In contrast to previous discrimination studies with clozapine-trained rats, the typical antipsychotic agents chlorpromazine and thioridazine and the serotonin antagonist ritanserin substituted for olanzapine. These results demonstrate that there are differences in the mechanisms underlying the discriminative stimulus properties of clozapine and olanzapine. Specifically, olanzapine's discriminative stimulus properties appear to be meditated in part by both cholinergic and serotonergic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Drug discrimination studies seem to support this notion (Goudie and Taylor, 1998; Porter et al , 2000a; Cole et al , 2007; Goudie et al , 2007). Using a two-lever drug discrimination paradigm, Porter et al (2000a) found that the dopamine D 2 antagonists chlorpromazine and thioridazine substituted for OLZ in producing OLZ-appropriate responding in rats, as did the muscarinic cholinergic antagonist scopolamine and the 5-HT 2A/2C serotonergic antagonist ritanserin. This finding suggests that the antagonism of either dopamine D 2 receptors, muscarinic receptors, or 5-HT 2A/2C receptors is sufficient to mimic the OLZ-induced interoceptive state.…”
Section: Discussionmentioning
confidence: 93%
“…Drug discrimination studies seem to support this notion (Goudie and Taylor, 1998; Porter et al , 2000a; Cole et al , 2007; Goudie et al , 2007). Using a two-lever drug discrimination paradigm, Porter et al (2000a) found that the dopamine D 2 antagonists chlorpromazine and thioridazine substituted for OLZ in producing OLZ-appropriate responding in rats, as did the muscarinic cholinergic antagonist scopolamine and the 5-HT 2A/2C serotonergic antagonist ritanserin. This finding suggests that the antagonism of either dopamine D 2 receptors, muscarinic receptors, or 5-HT 2A/2C receptors is sufficient to mimic the OLZ-induced interoceptive state.…”
Section: Discussionmentioning
confidence: 93%
“…CPZ and CLZ both produce full substitution (>80% LR) in rats trained to discriminate olanzapine from vehicle in a two-choice drug discrimination task (Porter and Strong 1996;Porter et al 2000a). Moreover, both CLZ and olanzapine have produced full stimulus generalization in rats trained to discriminate CPZ from vehicle (Porter et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…In support of the compound cue hypothesis, it has been reported that rats discriminating the putative antipsychotic S-16924, which acts at many receptors, generalize fully to clozapine, and that rats discriminating clozapine generalise reciprocally to S16924 . Furthermore, rats discriminating olanzapine, which also acts at many receptors, generalise to clozapine (Porter et al 2000a).…”
Section: Introductionmentioning
confidence: 99%